Problemas emocionales y los accidentes de tránsito en los Conductores de la Unión de Transportistas Terrestres de Quevedo, año 2019 - Castillo Arcos, Walter David (2019)
This research work dealt with the subject of: Emotional problems and traffic accidents in the drivers of the Union of transporters of Quevedo, a field investigation was carried out to the problem of the variable emotional problems in a sample of professional drivers. The main objective was to analyze the incidence of emotional problems in traffic accidents of drivers. The investigation was through a mixed approach, of a feasible type, in which deductive and inductive methods were used, among others, being a descriptive and bibliographic field investigation in which observation techniques and surveys applied to drivers and interviews were used. President, which supports the results obtained during the entire process of the final investigation report. The alternative that was obtained program for the solution of the problem was a psychological training with methods of relevance in primary prevention, in order to provide psychological preparation to drivers with emotional problems, where each of the drivers will have the proper and respective information on levels of anxiety, stress and the risk of emotional problems.